KEBIJAKAN PEMERINTAH TENTANG PENGELOLAAN SATUAN PENDIDIKAN KEAGAMAAN: Tantangan Terhadap Implementasi Manajemen Berbasis Sekolah - Siti Nur Hidayati (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2009)
The Government’s policy on educational management in Indonesia, (UUSPN No. 20.2003), promotes school autonomy through School Based Management (SBM). The system of the government as stated on PP No. 55 (2007) has also organized an implementation process of religious based school. However, the religious educational institutions are still under discrimination. In fact, Islamic educational institutions face the problem of curriculum, human resources, management, and financial. Therefore, the introduction of SBM is meant to develop the professionality and accountability of Islamic education.